Warcraft. Volume 1, Dragon hunt : the Sunwell trilogy - Knaak, Richard A. (Tokyopop, 2005)
Kalecgyos, a blue dragon, takes human form to investigate a mysterious power and encounters a vengeful dwarf, the army of the Undead Scourge, and Anveena, a beautiful young maiden.